Comissão intra-hospitalar de doação de órgãos e tecidos para transplantes: papel do enfermeiro - Tolfo, Fernando (2015)
The donation of organs and tissues for transplantation is being used to treat a wide range of diseases. The structure of the Brazilian transplant system is based on the search for potential donors and in this context, the Commissions Intra-hospital Donation of Organs and Tissues for Transplantation (CIHDOTT) play an important role in obtaining organs through active search potential donors. Among the members of CIHDOTT, is the nurse who has great importance in the donation process and organ transplantation. This study aimed to know the nurse's role as a member of Intra-hospital Committee on Organ Donation and Transplantation fabrics - CIHDOTT. This is a qualitative research, exploratory and descriptive. Was performed with nurses working in CIHDOTT five hospitals in Porto Alegre, the state capital of Rio Grande do Sul, Brazil. Data were collected through semi-structured interview, during the first half of 2014. The data were analyzed based on thematic content analysis framework proposed by Minayo. The results highlight four categories related to the role of the nurse in CIHDOTT: The insertion of nurses in CIHDOTT; Nurses work in CIHDOTT: Facilities and difficulties faced by nurses in the course of work in CIHDOTT. The work of nurses with relatives, particularly with respect to the reception and bond and the centrality of nurses who work in CIHDOTT. We conclude that the CIHDOTT nurse is fundamental, and is seen as crucial for a donation program and successful transplant. Is a professional to perform their role, appropriates technological, logistical and human resources in order to develop mainly the activities of coordination / management CIHDOTT, and direct and indirect assistance throughout the donation and transplantation process actions and attitudes aimed at the donor, to the care team and family.